Um sistema de intervenção computacional para rastreio e monitoramento de leitura em uma proposta de RTI - Zavaleta Gavidia, Jorge Juan (2017)
This thesis aims to present a system to monitor the intervention of children with specific reading disorders based on the RtI approach. The proposed architecture of DysDTool+L contains the RtI modules (layers 2 and 3), intervention strategies, severity (fuzzy and z score) and configuration. Specific texts are defined for each school year of the patients (2nd to 8th year), and experiments in both the RTI-2 layer with 70 patients and the RTI-3 layer with 21 patients. The variables used in the experiments are the reading speed and the deviation and are inputs of the fuzzy system and the z score that returns as output the degree of severity that determines the level of dyslexia severity of an intervention patient. The grade is measured at the beginning and end of the experiment during 16 weeks of a semester. The experiments indicate progress of patients using the RtI approach in most cases. However, further research should be done to determine if progress is product of the intervention strategies used or there are other factors. The discrepancies found should be analyzed by the specialist. The DysDTool+L is a tool for monitoring to help expert to dealing with dyslexia.